CHARACTER IN FICTION I LOVE THE MOST (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article describes the eighteen-year-old kid who serves as the main protagonist of the Harry Potter novels. He is a wizard and attends a magic school. The fact that he uses this talent to aid everyone sets him apart from other characters. and has a number of challenges in achieving this aim.